A note on Krugman's liquidity trap - Stefano Di Bucchianico (University of Massachusetts, Department of Economics, 2018)
The 1998 stylized model of Krugman constituted a ground-breaking contribution explaining the long lasting Japanese stagnation as the consequence of a "liquidity trap" situation featuring a negative natural interest rate. Our critique to such a proposal will focus on three aspects. First, we will question the logical structure of the model, providing an alternative interpretation of its closure. Second, we will argue that aggregate demand has no role in the explanation, as the cause for the persistent excess of savings over desired investment is the result of a supply side shock plus a financial rigidity on the nominal interest rate. Finally, we will discuss the restrictive assumptions needed to get a negative natural interest rate, the concept that lies at the foundation of the entire theoretical apparatus. Our conclusion is that the explanation offered within the 1998 contribution does not provide a satisfying rationale for the Japanese stagnation.
Keywords: E31; E40; E52; E58; 330; Liquidity trap; Japanese stagnation; natural interest rate